Perkembangan Pemikiran Hadis Kontemporer di Indonesia (Studi Hasil Penelitian di Jurnal Bereputasi Nasional Tahun 2015-2020) - Ach Baiquni (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Development of Contemporary Hadith Thought in Indonesia (Study of Research Results in a Journal of National Reputation 2015-2020)This paper aims at the development of Hadith thought in Indonesia and the contribution of Muslim Intellectual thought that exists in Islamic Universities in Indonesia. Because they have written articles on many topics of Hadith such as the content of Hadith, Hadith sciences, and some theories which relate to Hadith. This article uses a descriptive-analytical approach. Besides, the data are taken from several reputable Islamic and Hadith Sciences journals. In the conclusion, the article results that hadith studies in Indonesia in this contemporary era have experienced the development of the theme of their studies which initially only focused on the validity of hadith but later began to appear as integration between hadith and social sciences, health, science and others and their notions contribute to various Hadith Sciences topic, provide solutions to the problems in the society by applying the Hadith theories, and also re- study the culture that based on the message of Hadith in case to counter the thought that assumes that the culture is bid’ah. In addition, the notions of Hadith Experts become their own type in the development of Hadith in Indonesia and even in the world